CHARACTERISTICS OF THE MATHEMATICAL APPROACH TO MODELING THE ECONOMIC BEHAVIOR OF AN INDIVIDUAL DUE TO PSYCHOLOGICAL FACTORS - VOSKANYAN, KARLEN (Bulletin of Yerevan University E: Philosophy, Psychology, 2020)
The characteristic feature of every person as a social subject is their economic behavior. Economic behavior is a type of social behavior of the subject reflecting their participation in economic life through various forms of economic activity and due to the needs, interests, and material prosperity of the latter. It can be cognitive, impulsive, controlled, or uncontrollable. In most economic theories, when modeling the economic behavior of an individual, economic factors are considered as parameters of the characteristic functions of the model, while underplaying the role of psychological factors. In the manifestations of economic behavior, the dominant psychological factors are the biopsychological characteristics of the person. These factors, as genetic prerequisites, reflect the person’s attitude to the world and phenomena, their potentials, abilities, skills, predetermination, and orientation to an activity. The economic behavior of the individual is also determined by the characteristics of the society (ethnic group, nation) of which he or she is a representative. Factors influencing the economic behavior of an individual may be the ethnic characteristics (national traditions, customs, moral values, ethnic stereotypes, etc.). Therefore, when constructing a mathematical model of the economic behavior of an individual, among the parameters of the characteristic functions of the model, it is also necessary to consider factors of an ethnopsychological nature. For a more visual representation of the problem of modeling the economic behavior of an individual due to psychological factors, we consider the simplest mathematical model of a risk perspective built in a commodity-money space and discuss the possible manifestations of the economic behavior of an individual as a consumer in accordance with this model.